2012
DOI: 10.1021/ic202670v
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Reactivity and Coordination in Gallium(III) and Indium(III) Chloride Complexes With Geometrically Constrained Thio- and Selenoether Ligands

Abstract: Reaction of GaCl(3) with 1 mol equiv of [14]aneS(4) in anhydrous CH(2)Cl(2) gives the exocyclic chain polymer [GaCl(3)([14]aneS(4))] (1) whose structure confirms trigonal bipyramidal coordination at Ga with a planar GaCl(3) unit. In contrast, using [16]aneS(4) and GaCl(3) or [16]aneSe(4) and MCl(3) (M = Ga or In) in either a 1:1 or a 1:2 molar ratio produces the anion-cation complexes [GaCl(2)([16]aneS(4))][GaCl(4)] (2) and [MCl(2)([16]aneSe(4))][MCl(4)] (M = Ga, 3 and M = In, 4) containing trans-octahedral ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…20 All of the complexes containing mono-or simple acyclic dichalcogenoethers adopt distorted tetrahedral coordination environments, with a single chalcogen donor ligand, whereas using macrocyclic tetrathioethers or tetraselenoethers leads to higher chalcogen coordination at Ga, leading to five-or six-coordinate species. 24 While the thioether and selenoether complexes are stable under a dry N 2 -atmosphere, the telluroether complexes are more sensitive. No materials deposition studies on these types of reagents have been made prior to the present study.…”
Section: Resultsmentioning
confidence: 99%
“…20 All of the complexes containing mono-or simple acyclic dichalcogenoethers adopt distorted tetrahedral coordination environments, with a single chalcogen donor ligand, whereas using macrocyclic tetrathioethers or tetraselenoethers leads to higher chalcogen coordination at Ga, leading to five-or six-coordinate species. 24 While the thioether and selenoether complexes are stable under a dry N 2 -atmosphere, the telluroether complexes are more sensitive. No materials deposition studies on these types of reagents have been made prior to the present study.…”
Section: Resultsmentioning
confidence: 99%
“…5 DFT calculations predict that the bond lengths involving neutral ligands for a fixed metal (Al, Ga or In) generally increase (for gas phase molecules) Cl < Br < I, reflecting decreasing Lewis acidity down the series. 5,[7][8][9] However, in some cases solid state effects ( packing effects, intermolecular interactions, hydrogen bonding or interaction with solvent molecules) can mask this trend. 9 In order to explore the issue of size between Al and Ga centres, we compared d(M-X) (X = Cl, Br or I) for the fourcoordinate [MX 4 ] − ions, with data taken from the Cambridge Structural Database.…”
Section: Diarsine Complexesmentioning
confidence: 99%
“…The trend to higher coordination numbers found for aluminium(III) is thus an electronic effect, resulting from higher Lewis acidity towards phosphine ligands, as predicted by the DFT studies. 7,15…”
Section: Diarsine Complexesmentioning
confidence: 99%
“…or dinuclear [X 3 Ga(μ-L-L)GaX 3 ] (L-L = RS-(CH 2 ) 2 SR, MeSe(CH 2 ) 2 SeMe, MeTe(CH 2 ) 3 TeMe etc.). [11][12][13][14] Higher coordination numbers are rare in the gallium systems, but found with the thia-macrocycle [14]aneS 4 , ‡ which binds exodentate via two sulfur centres, affording the chain polymer [GaCl 3 ([14]aneS 4 )] with a trigonal bipyramidal geometry. 15 15,16 We have recently reported that [GaCl 3 ( n Bu 2 E)] (E = Se or Te) or [GaCl 3 {μ-n BuE(CH 2 ) n E n Bu)GaCl 3 ] are effective single source precursors for low pressure chemical vapour deposition (LPCVD) of Ga 2 E 3 thin films, and that preferential deposition occurs onto TiN in photolithographically patterned SiO 2 /TiN substrates.…”
Section: Introductionmentioning
confidence: 99%